Nickel and cobalt affect galactosylation of recombinant IgG expressed in CHO cells. - Prabhu, A.; Gadgil, M. (BioMetals, 2019)
Glycosylation is an important product quality attribute of antibody biopharmaceuticals. It involves enzymatic addition of oligosaccharides on proteins by sequential action of glycosyltransferases and glycosidases in the endoplasmic reticulum and golgi. Some of these enzymes like galactosyltransferase and N-acetylglucosaminyltransferase-I require trace metal cofactors. Variations in trace metal availability during production can thus affect glycosylation of recombinant glycoproteins such as monoclonal antibodies. Variability in trace metal concentrations can be introduced at multiple stages during production such as due to impurities in raw materials for culture medium and leachables from bioreactors. Knowledge of the effect of various trace metals on glycosylation can help in root-cause analysis of unintended variability in glycosylation. In this study, we investigated the effect of nickel and cobalt on glycosylation of recombinant IgG expressed in Chinese hamster ovary cells. Nickel concentrations below 500 µM did not affect glycosylation, but above 500 µM it significantly decreases galactosylation of IgG. Cobalt at 50 µM concentration causes slight increase in G1F glycans (mono galactosylated) as previously reported. However, higher concentrations result in a small increase in G0F (non galactosylated) glycans. This effect of nickel and cobalt on galactosylation of recombinant IgG can be reversed by supplementation of uridine and galactose which are precursors to UDP-Galactose, a substrate for the enzymatic galactosylation reaction.
Keywords: cobalt; Galactosylation; glycosylation; Nickel; Process variability; Trace metals

Engineering nucleotide sugar synthesis pathways for independent and simultaneous modulation of N-glycan galactosylation and fucosylation in CHO cells - Prabhu, Anuja; Shanmugam, Dhanasekaran; Gadgil, Mugdha (Metabolic Engineering, 2022)
Glycosylation of recombinant therapeutics like monoclonal antibodies (mAbs) is a critical quality attribute. N-glycans in mAbs are known to affect various effector functions, and thereby therapeutic use of such glycoproteins can depend on a particular glycoform profile to achieve desired efficacy. However, there are currently limited options for modulating the glycoform profile, which depend mainly on over-expression or knock-out of glyco-syltransferase enzymes that can introduce or eliminate specific glycans but do not allow predictable glycoform modulation over a range of values. In this study, we demonstrate the ability to predictably modulate the gly-coform profile of recombinant IgG. Using CRISPR/Cas9, we have engineered nucleotide sugar synthesis pathways in CHO cells expressing recombinant IgG for combinatorial modulation of galactosylation and fucosylation. Knocking out the enzymes UDP-galactose 4 `-epimerase (Gale) and GDP-L-fucose synthase (Fx) resulted in ablation of de novo synthesis of UDP-Gal and GDP-Fuc. With Gale knock-out, the array of N-glycans on recom-binantly expressed IgG is narrowed to agalactosylated glycans, mainly A2F glycan (89%). In the Gale and Fx double knock-out cell line, agalactosylated and afucosylated A2 glycan is predominant (88%). In the double knock-out cell line, galactosylation and fucosylation was entirely dependent on the salvage pathway, which allowed for modulation of UDP-Gal and GDP-Fuc synthesis and intracellular nucleotide sugar availability by controlling the availability of extracellular galactose and fucose. We demonstrate that the glycoform profile of recombinant IgG can be modulated from containing predominantly agalactosylated and afucosylated glycans to up to 42% and 96% galactosylation and fucosylation, respectively, by extracellular feeding of sugars in a dose-dependent manner. By simply varying the availability of extracellular galactose and/or fucose, galactosylation and fucosylation levels can be simultaneously and independently modulated. In addition to achieving the pro-duction of tailored glycoforms, this engineered CHO host platform can cater to the rapid synthesis of variably glycoengineered proteins for evaluation of biological activity.
Keywords: Antibody; Cell engineering; Fucosylation; Fx; Galactosylation; Gale; glycosylation; Nucleotide sugar synthesis; Recombinant therapeutics